Shape‐Memory Effect of Micro‐/Nanoparticles from Thermoplastic Multiblock Copolymers. Issue 1 (12th July 2013) - Wischke, Christian; Schossig, Michael; Lendlein, Andreas
<x xml:space="preserve">Abstract</x> The miniaturization and retained full shape‐memory functionality with particle switching to different predefined shapes is reported for semi‐crystalline multiblock copolymer matrices with all dimensions in the low micrometer‐range. A matrix size‐induced reduction of crystallinity suggests limitations of functionality in the low nanometer range. Applications as actuators in microdevices or as microcarriers with switchable shapes for modulated biorecognition are suggested.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>